Inflación del capital natural de la dehesa: hipótesis sobre la naturaleza caótica de la seca de los Quercus DENTRO DEL PROCESO DE LA SENESCENCIA FOLIAR - CUEVAS, S; TORRES, E; VÁZQUEZ, F.Mª.; López Arias, M; HERNÁNDEZ, A (III Congreso Forestal Español Congreso, 2001)
“Dehesa” is a gap forest yielding as an ecological-economic system (money-borrowed), poor soils (money-lender) upheld during optimal stopping millenia. Have supported multiple antropogenic nutrition disturbances during chaotic and resource routine affecting oak root uptake. Shoot nutrient odyssey is represented by cobweb model as price (nitrogen) evolution working by-product quantity (biomass). This trial evaluates cork oak (Quercus suber L.) and holm oak (Quercus rotundifolia Lam.) harvest basic sustainability (HBS) or nitrogen leaf redemption, southern Extremadura situated, evaluating ecological economic orientor for ecosystem. Defective HBS management hypothesis is expound in the absence of forest management, leading to sickly phenomenon on forest health as oak decline. Parallelly, HBS is proposed as an cork quality indirect index. Leaf senescence fork leads to physiological imbalance and, in some final cases, whole canopy defoliation (tie break). K.W.: Cobweb model, Oak decline, Renewal, Optimal stopping Dehesa, Nitrogen.
Keywords: Cobweb model; nitrogen; Oak decline; Optimal stopping Dehesa; Renewal

Afinidades bióticas entre encinares ibéricos en función de sus taxocenosis de acrídidos (Insecta, Orthoptera). - Presa, J J; Clemente, M E; HERNÁNDEZ, A; García, M D (Boln. Asoc. esp. Ent., 1999)
Orthopterocenosis from eight oak forests of the Iberian Peninsula are analyzed and compared. Two groups of biotopes are stablished: iberian-atlantic and iberian-mediterranean. Carrascal of Font Roja is excluded and reamins isolated, with a very low similarity index value with the other oak forests, because its peculiar characteristics. Use of orthopterocenosis in order to characterize specific biotopes is proposed
Keywords: holm oak forests (PG); orthopterocenosis